Crises, what crises? - Nauro F. Campos; Cheng Hsiao; Jeffrey B. Nugent (Institute for the Study of Labor (IZA), 2006)
Recent research convincingly shows that crises beget reform. Although the consensus is that economic crises foster macroeconomic stabilization, it is silent on which types of crises cause which types of reform. Is it economic or political crises that are the most important drivers of structural reforms? To answer this question we put forward evidence on trade and labour market liberalization from panel data on more than 100 developed and developing countries from 1950 to 2000. We find important differences in the effects of the two types of crises on the two reforms across regions and even from one measure of crisis to another. Yet, in general, we consistently find that political considerations (political crises as well as political institutions) are more important determinants of these reforms than economic crises. This finding is robust to the inclusion of interdependencies between the two types of crises, feedbacks between the two types of reform, the use of alternative measures of political and economic crises and whether or not the data are pooled across all countries or only across regions.
Keywords: H11; K20; E32; O40; 330; economic reform; economic crisis; political crisis; trade liberalisation; labour market reform; Wirtschaftskrise; Reform; Wirtschaftliche Anpassung; Arbeitsmarktpolitik; Außenhandelsliberalisierung; Welt